Alcohol-Impaired Driving: The Influence of Adverse Rearing Environments, Alcohol, Cannabis Use, and the Moderating Role of Anxiety. (21st March 2017) - Oshri, Assaf; Carlson, Matthew W.; Bord, Shiran; Zeichner, Amos
ABSTRACT: Background : The rate of alcohol-impaired driving (AID) increases during the college years and students who have reported adverse rearing environments appear to be at increased risk for the development of alcohol and drug use behaviors. Alcohol and cannabis are the most commonly used drugs by college students, and these substances are particularly predictive of substance-impaired driving. Objectives : The present study aimed to investigate whether adverse rearing environment experiences and level of alcohol and cannabis use are related to the frequency of alcohol-impaired driving and whether anxiety might buffer or accelerate this effect. Methods : Data regarding adversity, drug use, anxiety, and AID were obtained from 1, 265 students annually, from first to final year of college, over four waves (Mean Age at wave 1 = 18.5 years). Results : Structural equation modeling supported associations among childhood adversity, alcohol, cannabis, and anxiety symptoms. A significant mediation effect was found such that adversity was predictive of AID via alcohol use and cannabis use. Among men, anxiety symptoms accelerated the path from increased cannabis use and decelerated the path from increased alcohol use to AID frequency. Conclusions/Importance : Childhood adversity is a developmental risk precursor to drug use and AID, whereas anxiety might serve a risk or protective factor to AID, contingent on the drug used.